2009
DOI: 10.1002/hep.22665
|View full text |Cite
|
Sign up to set email alerts
|

Liver damage underlying unexplained transaminase elevation in human immunodeficiency virus-1 mono-infected patients on antiretroviral therapy #

Abstract: Liver damage associated with chronic unexplained high serum transaminases in human immunodeficiency virus (HIV)-infected patients under combined antiretroviral therapy is unknown. Liver histology was prospectively investigated in patients presenting serum transaminase elevation for more than 6 months, after exclusion of alcohol abuse, hepatitis C virus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 41 publications
7
96
1
4
Order By: Relevance
“…29 Although HAARTrelated NASH has thus far not been defined as a specific entity, there are data supporting the contribution of HAART to the development of liver steatosis which as a result can lead to inflammation and fibrosis. 112 Steatosis in HIV-infected patients has been reported to be independently associated with the use of dideoxynucleosides and occasionally of other NRTIs. [113][114][115][116][117][118] However, other studies have not found such an association.…”
Section: Acute Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Although HAARTrelated NASH has thus far not been defined as a specific entity, there are data supporting the contribution of HAART to the development of liver steatosis which as a result can lead to inflammation and fibrosis. 112 Steatosis in HIV-infected patients has been reported to be independently associated with the use of dideoxynucleosides and occasionally of other NRTIs. [113][114][115][116][117][118] However, other studies have not found such an association.…”
Section: Acute Eventsmentioning
confidence: 99%
“…123 However, some authors have found no correlation between mitochondrial function or DNA and the presence of NASH. 112 Steatosis may be part of a metabolic syndrome associated with HAART. Thus, hyperglycemia, overweight, and insulin resistance have been associated with liver steatosis in treatment-experienced HIV-infected patients.…”
Section: Acute Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A histological evaluation of a cohort of 20 HIV-monoinfected individuals with chronically increased LFTs demonstrated the presence of steatosis in 18 (60%) patients, of whom 16 (88.9%) had NASH and 13 (72.2%) had fibrosis [21]. Morse et al biopsied a cohort of 62 patients with similar features and found steatosis in 45 (73%), NASH in 34 (55%) and bridging fibrosis in 11 (17%) patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, other patients progress to nonalcoholic steatohepatitis (NASH), which occurs with excess inflammation and scarring, potentially causing severe damage to the liver. Indeed, many studies have found NASH in greater than 50% of HAART-treated patients undergoing liver histopathological assessments (Ingiliz et al 2009;Lemoine et al 2006;Akhtar et al 2008). HAART has been clearly shown to alter lipid and carbohydrate metabolism pathways, the underlying mechanism of NAFLD (Rector et al 2008).…”
Section: Hiv Pis Activate Er Stress In Hepatocytesmentioning
confidence: 99%